الاحتياجات التدريبية اللازمة أثناء الخدمة لمستشاري التوجيه والإرشاد المدرسي والمهني المدمجين حديثا من وجهة نظرهم – دراسة استكشافية– - صدقاوي كمال (جامعة الوادي - University of Eloued, 2023)
هدفت هذه الدراسة للكشف عن الاحتياجات التدريبية ومستوياتها لمستشاري التوجيه والإرشاد المدرسي والمهني المدمجين حديثا بقطاع التربية الوطنية حسب وجهات نظرهم. حيث قام الباحث باستخدام المنهج الوصفي، ولتحقيق الهدف من الدراسة قام ببناء استبيان الإحتياجات التدريبية يحوي عديد المهارات الواجب التدريب عليها، متكون من67 بندا، موزعة على ستة محاور ، وفق مقياس ليكرت الخماسي، متدرجة من موافق بشدة- معارض بشدة ، تم تطبيقه على عينة من مستشاري التوجيه والإرشاد المدمجين نهاية السنة الجامعية 20/2021، وبداية 21/2022، قدرت ﺑ 396 مستشار (ة) توجيه مدمج (ة)، وهذا بعد التحقق من ثباته وصدقه.. مستخدما البرنامج الإحصائي spss لتحليل البيانات واختبار صحة فرضيات الدراسة وقد توصلت الدراسة إلى النتائج التالية: - جل المستشارين المدمجين وبنسية تفوق 90%، لديهم إحتياجات تدريبية في كل الأنشطة المقترحة عليهم وبدرجة عالية. وعند إدخال متغيرات الدراسة وجد الباحث عدم وجود فروق ذات دلالة إحصائية في المحور الأول ، أما بقية المحاور فسجلنا وجود فروق دالة في متغير الجنس،أما متغير المؤهل العلمي اتضح عدم وجود فروق ذات دلالة إحصائية في خمسة محاور، أما محور الإعلام المدرسي فسجلنا للفروق دلالة إحصائية، أما المتغير الأخير التخصص وجدنا أن للفروق دلالة إحصائية في بعض المحاور و البعض ليس لها دلالة إحصائية وانطلاقا من النتائج المتوصل إليها خلص الباحث إلى مجموعة من الاقتراحات. This study aimed to reveal the training needs and levels of school and vocational guidance and counseling advisors newly integrated, according to their views. Where the researcher used the descriptive approach, and to achieve the goal of the study, he built a training needs questionnaire containing many skills to be trained on, consisting of 67 items, distributed over six axes, according to the five-point Likert scale, which was applied to a sample From the integrated guidance and counseling advisors at the end of the academic year 20/2021 and the beginning of 21/2022, it was estimated at 396, and this is after verifying its stability and validity. The study leads to the following results: Most of the integrated consultants, with a capacity of more than 90%, have training needs in all the activities proposed to them to a high degree., the researcher found that there were no significant differences in the first axis. As for the rest of the axes, we recorded the presence of significant differences in the gender variable. As for the educational qualification variable, it became clear that there were no significant differences in five axes. As for the school media axis, we recorded statistically significant differences. As for the last variable, specialization, we found that the differences have a statistical significance in some axes and some have no statistical significance
In-service training needs for newly integrated school and vocational guidance and counseling counselors from their point of view-an exploratory study
مقال
Keywords: مستشار التوجيه المدمج ، التدريب ، الاحتياجات التدريبية ، التدريب أثناء الخدمة ، الإدماج; Built-in guidance counselor, Training, Training needs, In-service training, Inclusion